Inhibitory and bactericidal power of mangosteen rind extract towards Porphyromonas Gingivalis and Actinobacillus Actinomycetemcomitans (Laboratory test) - Hendiani, Ina; Hadidjah, Dede; Susanto, Agus; Mustika SP, Indra (Padjadjaran Journal of Dentistry, 2016)
Introduction: The bacteria that cause the occurrence of pathogens of periodontal disease are gram negative anaerobes. These bacteria include Pophyromonas Gingivalis and Actinobacillus Actinomycetemcomitans. Mangosteen skin extract is known to have anti-inflammatory, anti microbial, and anti oxidant properties. The extract of the mangosteen peel is altered in gel preparation in order to streamline its clinical application in periodontal disease. The purpose of this study was to examine the antibacterial power of the ginger mangosteen tree extract gel against Pophyromonas gingivalis and Actinobacillus Actinomycetemcomitans (Aggregatibacter Actinomycetemcomitans). Methods: This research was conducted by experimental laboratory. Mangosteen fruit extract gel with concentration of 100%, 50%, 25%, 12,5%, 6,25%, 3,125% and 0,78% were tested against Pophyromonas Gingivalis and Aggregatibacter Actinomycetemcomitans with agar diffusion method. Results: The results of this study indicate that for Actinobacilus Aggregatibacter bacteria minimal inhibitory concentration at a concentration of 6.25% with a diameter of 13,5mm inhibition. Minimal bactericidal concentration at 12,5% concentration with 14,7mm inhibitory diameter. In the test of Pophyromonas Gingivalis bacteria, minimal inhibitory concentrations were obtained at a concentration of 1.56% and a minimum bactericidal concentration was obtained at a concentration of 3.125%. Conclusion: The conclusion that mangosteen peel skin gel extract can inhibit bacterial growth and is bactericidal against Pophyromonas Gingivalis and Actinobacillus Actinomycetemcomitans (Aggregatibacter Actinomycetecomitans).